Pengaruh Ukuran Perusahaan, Risiko Bisnis Dan Pertumbuhan Laba Terhadap Struktur Modal Pada Industri Otomotif - Noormansyah, Irvan; Setiawan, Wiwik (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This research aims to examine the effect of company size, business risk and profit growth on capital structure in the automotive industry. This research uses a quantitative approach, which is measured using a multiple linear regression-based method with SPSS Version 25.00. The population of this research is automotive sector companies listed on the Indonesia Stock Exchange for the period 2018 to 2021. The sample was determined using certain criteria, so the number of company samples for this research was 10 companies. Based on the analysis, it was found that the company size has a positive and significant effect on the capital structure, while business risk has a negative and significant effect on the capital structure and profit growth has a positive and significant effect on the capital structure in the automotive industry in Indonesia Stock Exchange 2018-2021.